2022
DOI: 10.1007/s00520-022-07128-w
|View full text |Cite
|
Sign up to set email alerts
|

Confounding factors in the assessment of oral mucositis in head and neck cancer

Abstract: Treatment of locally advanced head and neck carcinoma not amenable for surgical resection or resected with high-risk features is usually based on (chemo-)radiation treatment. Oral mucositis represents one of the main side effects of (chemo-)radiation, with an important impact on quality of life and causing approximately 20% of early interruption of treatment, leading to a suboptimal dose administered. Treatment and prevention of oral mucositis have a central role in the therapeutic pathways of head and neck ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
(72 reference statements)
0
3
1
Order By: Relevance
“…The mean age of the patients was similar 47.87±1.18 for the OM group and 47.36±1.25 for the patients without OM. As most of the women were of middle age our results were inconsistent with the previous literature as suggested by Lorini L et al that the risk developing OM is high in young age due to a faster rate of cell regeneration and also in old age due to a slower pace of healing process [ 13 ]. Our results showed that 60.2% of the patients who developed OM were of low socio-economic status and 58.3% of the patients from low socio-economic status did not develop OM.…”
Section: Discussioncontrasting
confidence: 99%
“…The mean age of the patients was similar 47.87±1.18 for the OM group and 47.36±1.25 for the patients without OM. As most of the women were of middle age our results were inconsistent with the previous literature as suggested by Lorini L et al that the risk developing OM is high in young age due to a faster rate of cell regeneration and also in old age due to a slower pace of healing process [ 13 ]. Our results showed that 60.2% of the patients who developed OM were of low socio-economic status and 58.3% of the patients from low socio-economic status did not develop OM.…”
Section: Discussioncontrasting
confidence: 99%
“…Treatment-related factors include radiation dose, technique, and site, etc. 27 A study 28 showed that compared with older patients (> 58 years), higher incidences and severity of OM in head and neck cancer after radiotherapy were observed in young patients (< 45 years). However, Merlano et al.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of mucositis is multifactorial, involving the interaction of various cellular and molecular events triggered by cancer treatments. A recent review summarized individual characteristics associated with the severity of oral mucositis induced by chemotherapy or radiation, including age, gender, oral hygiene status, salivary gland function, physiological parameters, and genetic characteristics [ 15 ]. A comprehensive exploration of the molecular pathogenesis of oral mucositis is beyond the scope of the current paper, but several recent reviews have elucidated advancements in our understanding of this topic [ 16 , 17 ].…”
Section: Oral Mucositismentioning
confidence: 99%